If x=(-2), y=1-(-11), z=6+(-2)+(-3), then find the following÷
(i)x^2y-1
(ii)yx^3z^2
(iii)2xz+(-3)z^2
(iv)7(y^2)×11x^2
(v)(x^2)(y^3)
Answers
Answered by
2
Step-by-step explanation:
Given:-
x=(-2), y=1-(-11), z=6+(-2)+(-3)
To find:-
Find the following÷
(i)x^2y-1
(ii)yx^3z^2
(iii)2xz+(-3)z^2
(iv)7(y^2)×11x^2
(v)(x^2)(y^3)
Solution:-
Given that :
x = -2
y= 1-(-11) = 1+11 = 12
z = 6+(-2)+(-3)=6-2-3=6-5=1
i) The value of x^2y-1
=>(-2)^2×12-1
=>4×12-1
=>48-1
=>47
ii) The value of yx^3z^2
=>(12)×(-2)^3×(1)^2
=>12×(-8)×1
=>-96
iii)The value of 2xz+(-3)z^2
=>2×(-2)×(1)+(-3)×(1)^2
=>-4+(-3)(1)
=>-4-3
=>-7
iv) The value of 7(y^2)×11x^2
=>7×(12)^2×11×(-2)^2
=>7×144×11×4
=>44352
v)The value of (x^2)(y^3)
=>(-2)^2×(12)^3
=>4×1728
=>6912
Answer:-
Answers for the following are :
i) 47
ii) - 96
iii) -7
iv)44352
v)6912
Similar questions
Social Sciences,
2 months ago
English,
2 months ago
English,
2 months ago
Hindi,
5 months ago
Math,
1 year ago